Consumption Attitude and Misconception on Protein Supplement among the Youths of Kathmandu Valley - Dangol, Subit (Nepalese Journal of Economics, 2024)
This study examines the consumption attitude and misconception on protein supplement among the youths of Kathmandu Valley. Consumption attitude and misconception is the dependent variable. Need of good nutrition consumption, knowledge on nutritional protein, exercise type, brand awareness, income level, and product attributes are the selected independent variables. The primary source of data is used to assess the opinions of respondents regarding need of good nutrition consumption, knowledge on nutritional protein, exercise type, brand awareness, income level, and product attributes. The study is based on 123 respondents from youths of Kathmandu valley. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of consumption attitude and misconception on protein supplement among the youths of Kathmandu Valley.The result showed that need of good nutrition consumption has a positive relationship with consumption attitude and misconception. It indicates that increase in need of good nutrition consumption leads to change in consumption attitude and misconception. Likewise, knowledge on nutritional protein has a positive relationship with consumption attitude and misconception. It indicates that good knowledge on nutritional protein leads to change in consumption attitude and misconception. Similarly, exercise type has a positive relationship with consumption attitude and misconception. It indicates that proper exercise type leads to change in consumption attitude and misconception. Furthermore, brand awareness has a positive relationship with consumption attitude and misconception. It indicates that increase in brand awareness leads to increase in consumption attitude and misconception. Moreover, income level has a positive relationship with consumption attitude and misconception. It indicates that increase in income level leads to increase in consumption attitude and misconception. Similarly, product attribute has a positive relationship with consumption attitude and misconception. It indicates that change in product attributes leads to change in consumption attitude and misconception.